The Effects of Utility Shutoff and Eviction Moratoria during the COVID-19 Pandemic on the Use of Alternative Financial Services Loans - Jennifer Andre; Breno Braga; Kassandra Martinchek; Signe-Mary McKernan (Institute of Labor Economics (IZA), 2024)
To protect financially distressed families during the COVID-19 pandemic, states implemented emergency measures such as moratoria on evictions and utility shutoffs. These policies prevented utility companies from disconnecting families' energy and water and landlords from obtaining court-ordered evictions for non-payment. Without these protections, consumers might have turned more often to high-cost alternative financial service (AFS) loans – such as payday loans - to pay their utility bills and rent. Using a random sample of 5 million consumers, we investigate whether moratoria on evictions and utility shutoffs impacted consumers' AFS use. Adults in states with an eviction or utility shutoff moratorium were less likely to borrow from high-cost non-banking institutions. Residents of high-poverty and Hispanic neighborhoods benefited the most from these protections. These results suggest that with such protections, families did not have to turn as often to high-cost loans to ensure access to housing and energy during financial distress.
Keywords: D14; D18; G51; 330; consumer protection policies; household finance; alternative financial services